2018
DOI: 10.1186/s12887-018-1271-z
|View full text |Cite
|
Sign up to set email alerts
|

Risk of low serum levels of ionized magnesium in children with febrile seizure

Abstract: BackgroundSuboptimal intake of magnesium become prevalent due to the modern diet of processed food low in magnesium. Magnesium may modulate seizure activity by antagonizing excitatory calcium influx through the N-methyl-D-aspartate receptor. Although hyponatremia has been reported to be common in febrile seizures, the most common form of seizure, little is known about the status of serum ionized magnesium. We therefore investigated the status of serum ionized magnesium (iMg2+) in children with febrile seizures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…11 The serum magnesium levels in febrile seizure group were lower than controls in the present study, the difference is significant. This was concordant with studies by Sherlin et al, 3 Namakin et al, 4 Salah et al, 24 and Sung -Jin Baek et al 25 A study by Bharathi et al, 22 found a positive correlation between hypomagnesemia to simple febrile seizure, with no significant association between serum magnesium level and atypical febrile seizure in children. However, few studies, 17,23,26 did not support the hypothesis that febrile seizure is related to reduced serum magnesium level.…”
Section: Discussionsupporting
confidence: 89%
“…11 The serum magnesium levels in febrile seizure group were lower than controls in the present study, the difference is significant. This was concordant with studies by Sherlin et al, 3 Namakin et al, 4 Salah et al, 24 and Sung -Jin Baek et al 25 A study by Bharathi et al, 22 found a positive correlation between hypomagnesemia to simple febrile seizure, with no significant association between serum magnesium level and atypical febrile seizure in children. However, few studies, 17,23,26 did not support the hypothesis that febrile seizure is related to reduced serum magnesium level.…”
Section: Discussionsupporting
confidence: 89%
“…However, further evidence is needed for the causal relationship between low magnesium and febrile convulsions. 13 Kannachamkandy et al studied 35 children between six months to five years with febrile seizures as cases and 35 children with febrile illnesses without seizures as controls and concluded that high serum copper levels and low serum magnesium levels were significantly associated with febrile seizures. 14 Sherlin et al included children between the ages of 6 months to 5 years with febrile convulsions and found that serum Magnesium levels were low in 32% of the cases with febrile convulsion indicating that serum Magnesium levels has got positive correlation in patients with febrile convulsion.…”
Section: Serum Magnesiummentioning
confidence: 99%
“…Some studies were excluded because they were not presented each mean ± SD, median, and IQR of magnesium and only presented the frequency of children with magnesium deficiency. Finally, 10 papers were included in the present systematic review 10‐13,18‐23 . All were case‐control or cross‐sectional.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, 10 papers were included in the present systematic review. [10][11][12][13][18][19][20][21][22][23] process is illustrated in Figure 1. The details of included studies are presented in Table 1.…”
Section: Search and Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation